(untitled) (Hilo Analítico, 2025)
Virtuality and digitality gave, and will continue to give, space to new digital tools, knowledge of new places and to establish emotional and sentimental relationships. Digital networks framed by the Internet open doors to infinite worlds of knowledge, details, academic, personal and social challenges, among others. Communicating to be with each other is an apparently simple process that is being put on the table today, why? For the simple fact of displacing presence and physicality for virtuality and digitality. Technological advances have taken humanity to unimaginable paths, changing understandings of the same world and the same universe. In the same way as the creation of soulless subjects called androids, which, if we continue as we are going, will displace us all from our spaces. This text is part of the reflections developed in the construction of the Doctoral Thesis entitled: The Place of Affections and the Links of Colombian Transnational Families: Temporalities and New Information and Communication Technologies